2011
DOI: 10.1186/ar3510
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of pregnancy complications in women who later develop scleroderma: a case control study

Abstract: IntroductionStudies have shown that fetal progenitor cells persist in maternal blood or bone marrow for more than 30 years after delivery. Increased trafficking of fetal cells occurs during pregnancy complications, such as hypertension, preeclampsia, miscarriage and intra-uterine growth restriction (IUGR). Women with these pregnancy complications are significantly more often HLA-class II compatible with their spouses. Women who later develop scleroderma also give birth to an HLA-class II child more often. From… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 15 publications
4
21
0
1
Order By: Relevance
“…Our observations confirm and extend an earlier retrospectively designed study (4). We found a significantly 69% increased risk of later scleroderma among women with preeclampsia.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our observations confirm and extend an earlier retrospectively designed study (4). We found a significantly 69% increased risk of later scleroderma among women with preeclampsia.…”
Section: Discussionsupporting
confidence: 91%
“…This study reported higher numbers of fetal origin microchimerism in women with scleroderma compared with healthy women (18). The study by van Wyk et al (4), and now also the present brief report, indirectly support the notion that fetal origin cells increase the risk of scleroderma, documented by an increased risk of scleroderma after preeclampsia. Both the quantity and type of cells acquired during pregnancy as well as other factors may have an impact on later maternal health (18).…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Previous epidemiologic investigations into the relationship between obstetric antecedents of subsequent rheumatic disease were based mainly on retrospective evaluations of obstetric history before the development of a definite rheumatic disease (26,27). Van Wyk et al have shown that, compared with healthy controls, the reproductive history of women who later developed SSc was characterized by increased rates of FGR and preeclampsia (28). Other retrospective studies of obstetric history before and after a diagnosis of SLE (29) suggested that preclinical SLE was associated with increased rates of FGR and pregnancy complications.…”
Section: Discussionmentioning
confidence: 99%
“…Many epidemiological studies have suggested that increased rates of adverse pregnancy outcomes can precede a definite diagnosis of ARD by years, suggesting that autoimmune diseases in early, undifferentiated, or incomplete states can negatively affect the reproductive outcome . A nationwide Danish cohort study on 1.9 million infants showed a reduction in birthweight and placental weight for infants born to women with preclinical AR, in addition to a 30% increased risk of preterm birth .…”
Section: Undifferentiated Connective Tissue Diseases and Pregnancy Oumentioning
confidence: 99%